Solution thermochemistry of Cuo and entropy of the aqueous cupric ion - Abajian, P.G.; Wulff, C.A. (Journal of Chemical and Engineering Data, 1969)
The heats of reaction of CuO-Cu(OH)2-H2O samples with aqueous HClO4 have been obtained as a function of concentration. Extrapolated to the normal standard state, the values are ΔH°298 = -15.00 and -15.37 kcal. per mole for CuO and Cu(OH)2, respectively. These data are consistent with thermochemical paths based on data in the literature. The entropy of Cu2+(aq) has been determined as -21.5 ± 1.5 cal. per mole 0 K. No evidence was obtained for stable “hydrates” of CuO in the H2O/CuO range 0 to 1.25. © 1969, American Chemical Society. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: dept.che

Nickel(II)-2,2′-Bipyridylamine System. I. Synthesis and Stereochemistry of the Complexes - Hurley, T.J.; Robinson, M.A. (Inorganic Chemistry, 1968)
The reaction of 2,2′-bipyridylamine (abbreviated BPAH) with divalent nickel salts results in the formation of several products, the type of which depends on the metal:ligand ratio and the coordinating ability of the associated anion. Thus, tetrahedral [Ni(BPAH)Cl2] and octahedral [Ni(BPAH)3] (ClO4)2 and [Ni(BPAH)2Cl2] have been isolated and characterized. In these complexes, dipyridylamine coordinates in a bidentate manner through the two pyridine nitrogens. Deprotonation of the amine at ambient temperature in butanol results in the conversion of the paramagnetic [Ni(BPAH)2Cl2] species into a six-coordinate polymeric material of the general formula Ni(BPA)2 where the deprotonated bipyridylamine moiety (ab¬breviated BPA) is coordinating in a tridentate manner with the amine nitrogen acting as a bridge. This polymer is cleaved quite readily by the action of water, pyridine, and, presumably, other complexing solvents. Deprotonation of [Ni(BPAH)-Cl2] at high temperatures in naphthalene or reaction of the deprotonated polymer with nickel(II) chloride, also at high temperatures, yields a red crystalline trinuclear complex of the molecular formula [Ni3(BPA)4Cl2]. Deprotonation of bis(2,2′-bipyridylamine)copper(II) chloride and bis(2,2′-bipyridylamine)palladium(II) perchlorate give the expected four-coordinate square-planar product. The deprotonated complexes of palladium, copper, and nickel are compared and corre¬lations are made between their ease of formation and the geometry and electronic arrangement of the central metal ion. © 1968, American Chemical Society. All rights reserved.
78 citations (Crossref) [2023-10-31]
Keywords: dept.che

The reaction of transition metal ions with n-(2-thiobenzothiazole)-2-pyridinaldimine - Natoli, F.S.; Robinson, M.A. (Inorganic and Nuclear Chemistry Letters, 1968)
6 citations (Crossref) [2023-10-31]
Keywords: dept.che

A Novel Synthesis of N, N', N''-Trisubstituted Guanidines - Gavin, D.F.; Schnabel, W.J.; Kober, E.; Robinson, M.A. (Journal of Organic Chemistry, 1967)
The action of phosgene on N, N'-disubstituted ureas is described in literature as giving a variety of products depending upon the reaction conditions. However, in no instance has the formation of N, N', N''-trisubstituted guanidines been reported from the above reaction. A novel synthesis is now presented in which these aforementioned guanidines are obtained. This reaction involves the phosgenation of N, N'-dialkyl- or N-alkyl-N'-arylureas at temperatures between 110 and 120° in an inert solvent such as monochlorobenzene. In the case of symmetrically disubstituted alkylureas, the N, N', N''-trialkylguanidines in the form of their hydrochloride salts are obtained. Unsymmetrically substituted ureas upon phosgenation also give guanidines, the type of which, in terms of their substituents, is dependent upon the ability of the urea nitrogen to act as a nucleophile as well as the steric nature of the substituent itself. Thus, phosgenation of N-cyclohexyl-N'-phenylurea gives N, N'-dicyclohexyl-N''-phenylguanidine exclusively. In cases where the substituents on nitrogen atoms of the urea molecule are alike in electron-donating abilities, product distributions are obtained, as with Ncyclohexyl-N'-isopropylurea. Where one urea nitrogen is strongly deactivated, as with N-cyclohexyl-N'-trifluoroethylurea, there is no indication of guanadine formation. Different types of compounds are isolated from these reactions. A mechanism is proposed to account for these observed patterns. Copyright © 1967, American Chemical Society. All rights reserved.
15 citations (Crossref) [2023-10-31]
Keywords: dept.che

An atomic and molecular orbital models kit - Stone, A.H.; Siegelman, I. (Journal of Chemical Education, 1964)
2 citations (Crossref) [2023-10-31]
Keywords: dept.che

Letter to the editor - Kuslan, L.I. (Journal of Chemical Education, 1962)
0 citations (Crossref) [2023-10-31]
Keywords: dept.che

Transition metal complexes of 2,6-disulphenamidopyridine and its schiff-base derivative with 2-pyridinaldehyde - Kaufman, Charles W; Robinson, Martin A (Journal of Inorganic and Nuclear Chemistry, 1968)
What would appear to be the simplest of the sulphur-containing pyridine ligands, 2-mercaptopyridine, gives complex, poorly-characterized derivatives with transition metal ions [1, 2]. The conversion of this compound to 2-sulfenamidopyridine and the latter's coordination to divalent metal ions yields complexes in which, in every reported instance, bonding is through the two nitrogen atoms [3]. The Schiff base derivatives of 2-sulphenamidopyridine also give species which conform to the expected mode of complexation[3]. The complexes of 2,6-dimercaptopyridine have also been reported[4]. As with the monosubstituted derivatives, no clearly defined structure has been reported, although these complexes are thought to be highly polymeric species. In this communication, the synthesis and pattern of complexation of 2,6-disulphenamidopyridine and its Schiff-base derivative with 2-pyridinaldehyde are investigated. Particular emphasis is placed on the structures of the nickel(II) analogs. © 1968.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-802-858-546-676 tex.type: [object Object]
Keywords: dept.che

Rensselaer and bridgewater: A footnote in the history of american scientific education - Kuslan, Louis I (Science Education, 1966)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-547-212-431-994 tex.type: [object Object]
Keywords: dept.che

Chemistry in some 19th century new england normal schools - Kuslan, Louis I (Science Education, 1962)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-011-936-335-543 tex.type: [object Object]
Keywords: dept.che